Forward Kinematics Analysis and Simulation for a Series Parallel Hybrid 7-DOF Humanoid Mechanical Arm based on MATLAB - Liu Jingjing; Peng Junquan; Liu Xinhua (Jixie chuandong)
A series parallel 7- DOF humanoid mechanical arm is designed and the mathematical model of humanoid mechanical arm is established through integration of kinematics analysis for parallel structure and D-H modeling method. The forward kinematics simulation of humanoid mechanical arm is carried out with Robotics toolbox of MATLAB,and then the continuous and smooth planning curves of joints angel and the Cartesian space trajectory of wrist are obtained. The simulation results show that the design parameters of humanoid mechanical arm are reasonable and can provide the basis for the optimal design of humanoid mechanical arm.